KEMAMPUAN TANAMAN GENJER (LIMNOCHARIS FLAVA (L.)BUCH.) MENYERAP LOGAM BERAT TIMBAL (PB) LIMBAH CAIR KERTAS PADA BIOMASSA DAN WAKTU PEMAPARAN YANG BERBEDA - HARYATI, MAHARANI (Universitas Negeri Surabaya, 2012)
The Paper Industry produces minor product in the form of sewage especially liquid sewage in a very large volume which contains of heavy metals Pb. Furthermore, this sewage is usually discharged into the water which causes pollution. An effort is required to minimize the content of Pb metal before being discharged into waters, including the use of Genjer plants as the agent of phytoremediation. This study aims to determine the ability of Genjer plants to absorb the Lead metals (Pb) from liquid paper waste. The research is accomplished by doing an experiment that uses a Randomized Block Design (RGD) with two treatment factors, the biomass plant and length of exposure time. The treatment factor of plant biomass is 0 g, 50 g, 100 g and 150 g. The factor of exposure time is for 7 days, 14 days and 21 days. The parameters which are observed include the levels of Pb in the liquid paper waste, in roots of Genjer plants and leaves of Genjer plants. The analysis of Pb levels uses ICP that is done at the Energy Studies and Engineering Laboratory, Sepuluh November Institute of Technology (ITS), Surabaya. The data are statistically analyzed using 2-way Anava and further test, Duncant Multiple Range Test (DMRT). The result shows that biomass of Genjer plants and exposure time affect to the ability of Genjer plants to absorb Pb metals in liquid paper waste paper. The most optimal decrease of Pb levels occurs in the treatment of biomass Genjer 150 grams with exposure time for 21 days which is equal to 0.4688 mg / l (80.09%). Genjer plants can absorb and accumulate Pb. The highest accumulation of Pb in the root is 1.1546 mg / l (26.1%), and in the leaves is 0.1120 mg / l (21.9%), both occur at 150 g biomass treatment and exposure time of 21 days. Thus the Genjer plant can be used as fitoremediator heavy Lead metal (Pb) in the liquid paper waste.